Evolution of Minimally Invasive Coronary Artery Bypass Grafting: Learning Curve. Issue 2 (March 2018) - Andrawes, Peter A.; Shariff, Masood A.; Nabagiez, John P.; Steward, Richard; Azab, Basem; Povar, Natasha; Sarza, Mirala; Demissie, Seleshi; Sadel, Scott M.; Nichols, Michele; McGinn, Joseph T.
Objective: Minimally invasive coronary surgery approach for coronary artery bypass grafting is a safe and reproducible procedure for multivessel revascularization. This study reviewed a single surgeon's experience with minimally invasive coronary surgery coronary artery bypass grafting, including operative time, number of bypasses, and conversion to sternotomy. Methods: A prospective database of consecutive minimally invasive coronary surgery coronary artery bypass grafting procedures from 2005 to 2013 was reviewed. A small anterolateral left thoracotomy allowed left internal mammary artery harvest, proximal anastomoses on the ascending aorta, and distal coronary anastomoses. Early cases were compared with the later cases, focusing on grafting strategies that led to a standardized approach with Propensity Score Matching analysis. Results: Seven hundred consecutive cases were divided into early (1–200) and late (201–700) groups. In the late group, the number of triple-vessel disease patients trended higher (50% vs. 57%, P = 0.0674) and the number of bypasses increased (2.3 ± 0.8 vs. 2.7 ± 1.0, P < 0.0001). Conversion to sternotomy significantly decreased between the groups (6% vs. 0.6%, P < 0.0001). There was no difference in rate of postoperative complications between the groups except for prolonged intubation (10% vs. 5%, P = 0.0236) and shortened length of stay (5.9 ± 6.7 vs. 5.5 ± 6.0, P = 0.0268). Propensity score matching analysis (n = 177) was significant for total bypass performed and time per bypass ( P < 0.05). The late group was further divided into subgroups of one hundred each (subgroup 1 through 5). Operative times differed significantly (subgroup 1: 249 ± 71.2, subgroup 2: 259 ± 85.8, subgroup 3: 244 ± 71.0, subgroup 4: 270 ± 58.4, and subgroup 5: 246 ± 47.9, P < 0.005). Conclusions: As experience with minimally invasive coronary surgery coronary artery bypass grafting increased, the ideal sequence of steps to optimize surgical outcome was defined. The number of bypassed vessels increased and the operative time and conversion to sternotomy decreased.